2009
DOI: 10.1073/pnas.0904187106
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 induces PGC-1α and regulates carbohydrate and fatty acid metabolism during the adaptive starvation response

Abstract: The liver plays a crucial role in mobilizing energy during nutritional deprivation. During the early stages of fasting, hepatic glycogenolysis is a primary energy source. As fasting progresses and glycogen stores are depleted, hepatic gluconeogenesis and ketogenesis become major energy sources. Here, we show that fibroblast growth factor 21 (FGF21), a hormone that is induced in liver by fasting, induces hepatic expression of peroxisome proliferatoractivated receptor ␥ coactivator protein-1␣ (PGC-1␣), a key tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
570
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 632 publications
(621 citation statements)
references
References 49 publications
(79 reference statements)
27
570
9
Order By: Relevance
“…Our studies show that FGF21 stimulates AMPK and SIRT1 activities in adipose tissue. Recently, FGF21 was found to increase PGC-1α expression, fatty acid oxidation, and TCA cycle flux in the liver (30). It would be of interest to determine whether FGF21 also can activate AMPK and SIRT1 to act in concert with PGC-1α in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies show that FGF21 stimulates AMPK and SIRT1 activities in adipose tissue. Recently, FGF21 was found to increase PGC-1α expression, fatty acid oxidation, and TCA cycle flux in the liver (30). It would be of interest to determine whether FGF21 also can activate AMPK and SIRT1 to act in concert with PGC-1α in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that adipose derived stem cells (ADSCs) show beneficial effects to improve liver fibrosis 4. In addition, fibroblast growth factor (FGF) 21 improves lipid profiles and hepatic steatosis 5. To enhance the therapeutic effects of ADSCs on liver fibrosis, we established FGF21‐secreting ADSCs (FGF21_ADSCs) and investigated their effects on thioacetamide (TAA)‐induced liver fibrosis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Rodent studies have shown that during fasting FGF-21 stimulates hepatic fatty acid oxidation, ketogenesis, lipolysis and gluconeogenesis to supply metabolically active tissues with substrates [3,4]. However, another animal study showed that in the fasting state FGF-21 inhibits lipolysis, whereas in the fed state FGF-21 stimulates it [5].…”
Section: Introductionmentioning
confidence: 99%